A Biodiversity Hotspot Losing Its Biocultural Heritage: The Challenge to Biocultural Conservation of Brazilwood (Paubrasilia echinata) - Bastos, Juan Gomes; Kury, Lorelai; Hanazaki, Natalia; Capozzi, Rebeca; Fonseca-Kruel, Viviane Stern da (Frontiers in Forests and Global Change, 2022)
The biocultural heritage of a region is developed and adapted after centuries of interrelationships between humans and nature. The endangered brazilwood [Paubrasilia echinata (Lam.), E. Gagnon, H.C. Lima, and G.P. Lewis] is a flagship species with cultural and economic importance that is directly affected by the history of human occupation on the Brazilian coast from the Portuguese colonization beginning in the 16th century onward. Despite its historical–cultural relevance, the lack of effective management and the anthropic pressure in coastal areas of the Brazilian Atlantic Forest (BAF; one of the terrestrial hotspots for biodiversity conservation) has led to the fragmentation of landscape connectivity and drastic degradation of the knowledge associated with biodiversity, including that of brazilwood, which also affects the biocultural diversity of the region. In southeastern Brazil, in the region of Cabo Frio, state of Rio de Janeiro, there are fragments of forest remnants with genetically ancient populations of brazilwood (possibly from the colonization period). The recognition of this valuable natural and cultural heritage induced the establishment of protected areas (PAs) in this region in 1986. Here, we studied how the increase in urbanization can affect the biocultural heritage of a flagship species even those close to protected areas. In nearby areas with populations of brazilwood, we interviewed residents from three communities, namely, Peró and Jacaré (municipality of Cabo Frio), and José Gonçalves (municipality of Armação dos Búzios). We conducted semi-structured interviews and free lists using visual stimuli to understand the current knowledge on this species. Thus, we verified socio-ecological dissociation, both inside and outside the PAs. This indicates a possible threat of losing the local knowledge network and the native populations of brazilwood in these areas, which consequently reveals the weaknesses of the current management models of the local PAs. Despite this, we showed that residents are interested in increasing local mobilization, awareness, environmental education, and reforestation actions aimed at the biocultural conservation of the species that gives the country its name, as well as that of the Atlantic Forest biome.